1997
DOI: 10.1091/mbc.8.4.755
|View full text |Cite
|
Sign up to set email alerts
|

sn-1,2-diacylglycerol and choline increase after fertilization in Xenopus laevis.

Abstract: sn-1,2-Diacylglycerol (DAG) mass and translocation of protein kinase C a and ,B to a membrane fraction increased -7 min after insemination of Xenopus laevis eggs. The DAG mass increase of 48 pmol (from 62 to 110 pmol/cell) was greater than that for inositol 1,4,5-trisphosphate (1P3; an increase of -170 fmol or -280-fold smaller than the DAG increase), and DAG peaks -5 min after IP3. Choline mass (a measure of phosphatidylcholine-specific phospholipase D) also peaked before DAG and the choline increase (134 pmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 45 publications
7
56
2
Order By: Relevance
“…Studies have revealed that PtdIns(4,5)P 2 itself binds to a polybasic region in the C2 domain of PKC (32,33). Studies have shown that eleven PKC isozymes are present in Xenopus oocytes (21,22). We detected PKC ␣, ␤I, ␤II, ␦, and ⑀ isozymes in this present study (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Studies have revealed that PtdIns(4,5)P 2 itself binds to a polybasic region in the C2 domain of PKC (32,33). Studies have shown that eleven PKC isozymes are present in Xenopus oocytes (21,22). We detected PKC ␣, ␤I, ␤II, ␦, and ⑀ isozymes in this present study (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…PKC ␤II May Be Involved in the Effects of Membrane Depolarization-Previous studies indicate that all 11 known mammalian isozymes of PKC are present in Xenopus oocytes (21,22). However, after trying antibodies from different sources, we were only able to detect the presence of the PKC ␣, ␤I, ␤II, ␦, and ⑀ isozymes.…”
Section: Pma Mimics the Effects Of The Membrane Depolarization-inmentioning
confidence: 86%
“…Raz et al (1998) demonstrated the relocalization of cPKC isotypes PKC-α and -β during the activation of rat oocytes. The activation of isotypes PKC-α a -β was also reported to occur during the activation of Xenopus oocytes (Stith et al, 1997). In our experiments, however, the activation of oocytes was not blocked either by hispidin (inhibitor of PKC-β) or by Go6976 (inhibitor of PKC-α, -β I ).…”
Section: Discussioncontrasting
confidence: 52%
“…In support of this, choline, another product of PC hydrolysis by PLD, is also accumulating in a similar time course of fertilization. Whether DG is involved in the activation of egg PKC remains to be clarified (Stith et al 1997). Production of DG has also been examined in mouse eggs (Stith et al 1997;Yu et al 2008).…”
Section: Sn-12-diacylglycerol (Dg)mentioning
confidence: 99%
“…Whether DG is involved in the activation of egg PKC remains to be clarified (Stith et al 1997). Production of DG has also been examined in mouse eggs (Stith et al 1997;Yu et al 2008). In this species, sperm-derived PLC seems to be mainly responsible for DG production and subsequent PKC activation.…”
Section: Sn-12-diacylglycerol (Dg)mentioning
confidence: 99%